SUBJECTIVITY AND MULTIDIMENSIONAL WRITING IN JORGE EDUARDO EIELSON POETRY - Morillo Sotomayor, Alex (2021)
The specialized criticism about Jorge Eduardo Eielson poetry is used to identify a break or silence between the series written from 1958 to 1960, made up of the collections Eros / iones, 4 estaciones, Papel and Canto visible, and his later poetry; what has been explained as a gesture, on the part of the poet, of dissatisfaction and, even, of resignation to the words. This reflection points to the limitations of this readings, since I recognize in poetry collections such as Ceremonia solitaria (1964), specially "Ceremonia solitaria en compañía de mí mismo", which reveals the sign of continuity that consists in the realization of a type of poem defined here as multidimensional and that reveals, rather than a renunciation, an attempt to recalculate the expressive and imaginative scope of words. It will be stated that the multidimensionality of the self fuses and diversifies the senses of the masculine and feminine, as part of an integrating vision of human nature and how this multidimensional self deconstructs the language and text conditions that sustain the poem.